2001
DOI: 10.1038/sj.mp.4000801
|View full text |Cite
|
Sign up to set email alerts
|

Extrapyramidal symptoms and antidepressant drugs: neuropharmacological aspects of a frequent interaction in the elderly

Abstract: Depression is the most prevalent functional psychiatric disorder in late life. The problem of motor disorders associated with antidepressant use is relevant in the elderly. Elderly people are physically more frail and more likely to be suffering from physical illness, and any drug given may exacerbate pre-existing diseases, or interact with other drug treatments being administered for physical conditions. Antidepressants have been reported to induce extrapyramidal symptoms, including parkinsonism. These observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 58 publications
(66 reference statements)
1
17
0
Order By: Relevance
“…Thus, results from experiment 1 showed that FLX administration exacerbates Parkinsonian-like motor dysfunctions induced by a low dose of TBZ in rats. These results are consistent with studies showing potentiation of haloperidol-induced motor impairments (eg, catalepsy and bradykinesia) by FLX in rodents (Tatara et al, 2012), and with numerous clinical reports linking motor side effects and worsening Parkinsonism with FLX treatment of depression (Leo, 1996;Gerber and Lynd, 1998;Govoni et al, 2001;Madhusoodanan et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus, results from experiment 1 showed that FLX administration exacerbates Parkinsonian-like motor dysfunctions induced by a low dose of TBZ in rats. These results are consistent with studies showing potentiation of haloperidol-induced motor impairments (eg, catalepsy and bradykinesia) by FLX in rodents (Tatara et al, 2012), and with numerous clinical reports linking motor side effects and worsening Parkinsonism with FLX treatment of depression (Leo, 1996;Gerber and Lynd, 1998;Govoni et al, 2001;Madhusoodanan et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Yet, controlled clinical trials, metaanalyses, and systematic review collectively suggest that SSRIs are no more effective than placebo in treating depression in the context of PD (Skapinakis et al, 2010;Aarsland et al, 2009). Furthermore, SSRI administration has been associated with a number of motor side effects, and may be implicated in increased motor disability in PD patients (Leo, 1996;Richard et al, 1997;Govoni et al, 2001;Veazey et al, 2005;Aarsland et al, 2009). There are presently more than 100 published reports of 'extrapyramidal' symptoms (eg dystonia, akathisia, dyskinesia, and Parkinsonism, including tremor) associated with SSRI treatment; fluoxetine (Prozac; ( ± )-N-methyl-γ-[4-(trifluoromethyl)phenoxy]benzenepropanamine hydrochloride; FLX) has been implicated in the majority of these reports (Madhusoodanan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies were negative, probably not surprisingly given the lack of theoretical basis for such combination in EPS. Moreover, the SSRIs are reported to even cause EPS in patients with major depressive disorder ( Govoni et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…These cases have not escaped the awareness of clinician authors, and as such, several reviews have been published over time. [4][5][6][7][8][9][10][11][12][13][14] Typically, EPRs are related to antipsychotic treatment and are believed to be related to postsynaptic dopamine-2 (D2) receptor antagonism in the nigrostriatum. As a result, patients who are treated with an antipsychotic are routinely monitored for the development of one, or more, EPR.…”
Section: Introductionmentioning
confidence: 99%